Synthesis and investigation of novel 6-(1, 2, 3-triazol-4-yl)-4-aminoquinazolin derivatives possessing hydroxamic acid moiety for cancer therapy. Issue 1 (1st January 2017) - Ding, Chao; Chen, Shaopeng; Zhang, Cunlong; Hu, Guangnan; Zhang, Wei; Li, Lulu; Chen, Yu Zong; Tan, Chunyan; Jiang, Yuyang
Graphical abstract: Highlights: 6-(1, 2, 3-Triazol-4-yl)-4-aminoquinazolins were designed and synthesized. Final compounds displayed outstanding inhibitory activity on EGFR, HER2 and HDAC. Compounds9b and9d showed potent activity against five cancer cell lines. Compound9d regulated the cellular level of p-EGFR, p-HER2 and histone H3. Compound9d induced remarkable apoptosis in BT-474 cells. Abstract: By merging the critical pharmacophore of EGFR/HER2 and HDAC inhibitors into one compound, a novel series of EGFR, HER-2, and HDAC multitarget inhibitors were synthesized. Compounds9a –l contained 4-anilinoquinazolines with C-6 triazole-linked long alkyl chains of hydroxamic acid and displayed excellent inhibition against these enzymes (compound9d exhibited the best inhibitory potency on wild-type EGFR, HDAC1, and HDAC6 with IC50 values 0.12 nM, 0.72 nM and 3.2 nM individually). Furthermore, compounds9b and9d potently inhibited proliferation of five human cancer cell lines (with IC50 values between 0.49 and 8.76 μM). Further mechanistic study revealed that compound9d also regulated the phosphorylation of EGFR and HER2 and histone H3 hyperacetylation on the cellular level and induced remarkable apoptosis in BT-474 cells. Therefore, our study suggested that a system network-based multi-target drug design strategy might provided an alternate drug design method, by taking into account the synergy effect of EGFR, HER-2 and HDAC.